Master tracks in different resolutions of ALKOR cruise AL623a, Kiel - Kiel, 2024-11-09 - 2024-11-11 - Clara Seidel (PANGAEA, 2025)
Raw data acquired by position sensors on board RV Alkor during expedition AL623a were processed to receive a validated master track which can be used as reference of further expedition data. During AL623a data from the motion reference unit Kongsberg MRU-Z, the Trimble MPS865 GPS receiver, the Furuno GP-170 and Furuno GP-150 GPS receivers and from the NAVIGAT X MK 1 gyro compass were used to calculate the mastertrack. Data were downloaded from DAVIS SHIP data base (http://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.